(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This scholarly article investigates the comparative characteristics of synonymous and antonymous phraseological units (PUs) within the broader field of phraseology, a vital sub-discipline of linguistics. Phraseological units, often known as idioms, proverbs, and set expressions, serve as fixed verbal structures with figurative meanings, frequently deviating from the literal interpretations of their components. Synonymy and antonymy, as key semantic relationships, are well-studied in general lexical semantics, but their manifestation within phraseology introduces additional layers of complexity, especially due to idiomatic opacity, cultural specificity, and structural fixity. The study aims to analyze how synonymous and antonymous PUs function in everyday communication, enhance stylistic richness, and reflect cultural worldviews. Particular emphasis is placed on cross-linguistic comparison, primarily between English and Uzbek, to reveal universal and language-specific features of phraseological synonymy and antonymy. The paper also explores the functional roles of these units in speech — including expressiveness, emphasis, and rhetorical contrast — as well as their pedagogical implications for language learning, translation, and intercultural communication. By offering theoretical explanations supported by practical examples, this article contributes to both the theoretical development of phraseology and its practical application.